Evaluation of Interferon Alpha (IFN-α) in Women with Systemic Lupus Erythematosus in Iraq - Abdulridha, Ruaa Hameed; Saud, Asmaa Mohammed; Alosami, Mohammed Hadi (Iraqi Journal of Science, 2022)
Systemic Lupus Erythematosus (SLE) is a multifactorial chronic systemic autoimmune disease. It is characterized by a lack of immune tolerance to autoantigens such as nuclear antigens. The aim of the study is to assess the interferon-alpha (IFN-α) serum level in Iraqi patients with SLE and determine its potential relation to different clinical and laboratory parameters and disease activity. 100 SLE patients were all females and with a mean of age 31.3 ± 10 years (16-63years) and disease duration of 5.8 ± 3.7years (1 month to 15 years). The average of SLEDAI score ranged from 2 to 22 with a mean of (8.53 ±3.42). Proteinuria, ESR, creatinine and AST were significantly higher (65% vs. 10% and 0.62±0.11 vs. 0.70±0.14 mg/dl respectively) while the PLT was significantly lower (231.9±88.8 vs. 282.3±67.3 103/mL) (p< 0.001) among SLE patients as compared to control. Serum levels of IFN-α were increased in the SLE patients compared to control, and no significant difference has been observed (208.7±530.0 vs. 63.7±34.8 pg/ml) respectively (P=0.245). Interferon-alpha showed a significant negative correlation with the SLE Disease Activity Index (SLEDAI) in the active and inactive groups. There were no significant variations in all study parameters across IFN-α serum levels (p greater than 0.05). In conclusion, the results suggest a risk effect for female gender and age in etiology of SLE. IFN-α could not be considered as biomarker or to have a risk effect in SLE patients or perpetuate the disease activity. No evidence for any correlation between the IFN-α serum level and any clinical manifestations or laboratory investigation of the disease in current study except for age and disease duration, which suggests them as a risk factor for increasing the IFN-α serum level.